2013
DOI: 10.1017/s1474745612000638
|View full text |Cite
|
Sign up to set email alerts
|

The TBT Panels: US–Cloves, US–Tuna, US–COOL

Abstract: In a series of controversial 2011 decisions, WTO DSM Panels sought to reconcile legitimate regulatory interests of the state with various obligations to treat imported products in an even-handed and not unnecessarily trade-restrictive manner. Among the key points of contention were which obligation pertained in each case – national treatment, limits on technical regulations, or rules governing standards. In each case, the Panel imposed significant restrictions on national regulatory practices, and in each case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 11 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…Indonesia’s complaint targeted a US ban on the sale of flavoured cigarettes, aimed at reducing tobacco consumption amongst young people, by eliminating flavorings, although importantly, menthol cigarettes were not banned. Indonesia argued that the legislation unfairly discriminated against their exports of clove cigarettes, compared to menthol cigarettes, which were primarily made in the US (Howse and Levy 2013). The core of this case was therefore, not the question of whether the US had the right to ban certain tobacco products, but whether menthol and clover cigarettes are ‘like products’ and thus should be accorded equal treatment (Flett 2013).…”
Section: An Empirical Account Of the Plain Packaging Casementioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia’s complaint targeted a US ban on the sale of flavoured cigarettes, aimed at reducing tobacco consumption amongst young people, by eliminating flavorings, although importantly, menthol cigarettes were not banned. Indonesia argued that the legislation unfairly discriminated against their exports of clove cigarettes, compared to menthol cigarettes, which were primarily made in the US (Howse and Levy 2013). The core of this case was therefore, not the question of whether the US had the right to ban certain tobacco products, but whether menthol and clover cigarettes are ‘like products’ and thus should be accorded equal treatment (Flett 2013).…”
Section: An Empirical Account Of the Plain Packaging Casementioning
confidence: 99%
“…The core of this case was therefore, not the question of whether the US had the right to ban certain tobacco products, but whether menthol and clover cigarettes are ‘like products’ and thus should be accorded equal treatment (Flett 2013). Although Indonesia did indeed supply the vast majority of clove cigarettes to the US market prior to the ban (Howse and Levy 2013), the market for clove cigarettes in the US was tiny (Jarman et al 2012). At their peak in 2007, ITC figures indicate that US imports of clove cigarette from Indonesia were $16,6m, a rather low level of trade to justify such a costly undertaking as a WTO challenge.…”
Section: An Empirical Account Of the Plain Packaging Casementioning
confidence: 99%
“…Shortly before the final COOL rule was implemented, the Canadian and Mexican governments filed a request for consultations at the WTO in December 2008 and June 2009 respectively, and both countries requested a panel in October 2009. The subsequent Panel Report and Appellate Body Report found that the COOL regulation breached the TBT agreement by offering less favorable treatment to foreign goods (Howse and Levy, 2013;Mavroidis and Saggi, 2014). In July 2012, the DSB adopted the Appellate Body's Report.…”
Section: The United States Cool Regulation and Earlier Phases Of The mentioning
confidence: 99%
“…However, as stated by Howse and Levy, ‘the perfect ought not to be the enemy of the good’ (Howse and Levy, 2013: 341). The recommendations made here are based in a slightly different universe, in which Panels are always supplied with sufficient and high-quality evidence from the Parties and WTO Panels have sufficient economic expertise to evaluate this evidence in a rigorous manner.…”
Section: Assessing Competitive Relationships Under the National Treatmentioning
confidence: 99%